2008
DOI: 10.1016/j.bbmt.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Peripheral Blood Stem Cell Yield in Volunteer Donors Mobilized with Granulocyte Colony-Stimulating Factors: The Impact of Donor Characteristics and Procedural Settings

Abstract: Peripheral blood stem cells (PBSCs) are increasingly used as the source of hematopoietic stem cells, but there are large variations in harvest outcome between individuals mobilized by granulocyte colony-stimulating factor (G-CSF). We examined the effects of donor characteristics and procedure factors on the day 1 CD34+ cell yield in 373 unrelated healthy donors. G-CSF was administered subcutaneously at a planned dose of 8.3 to 11 microg/kg daily for 5 days, followed by harvest started on day 5 of G-CSF treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 21 publications
8
69
2
Order By: Relevance
“…Similar to reports by other authors [6,13,[23][24][25] our data show strong association between donor age of 55 years or more and reduced PBSC mobilization.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to reports by other authors [6,13,[23][24][25] our data show strong association between donor age of 55 years or more and reduced PBSC mobilization.…”
Section: Discussionsupporting
confidence: 82%
“…A different interaction to G-CSF between genders had been suggested. We had recently demonstrated that female gender had a higher risk (odds ratio = 3.01) for having a poor stem cell yields than other donor characteristics [12]. However, the marrow cell densities were not different between two genders in present study.…”
Section: Discussionmentioning
confidence: 44%
“…G-CSF (Filgrastim, Kirin Brewery Co., Tokyo, Japan) was given subcutaneously at dosage of 10 μg/kg per day for 5-6 consecutive days. The actual G-CSF dose was adjusted to fit the combination of available dosage forms in our institute [7]. The first 4-5 doses of G-CSF were administrated at local clinics near donor's residence.…”
Section: Donors and Stem Cell Mobilizationmentioning
confidence: 99%